Green Entrepreneurial Marketing Orientation and Sustainable Performance in SMEs: A Systematic and Bibliometric Synthesis of Emerging Trends and Research Opportunities - Lova, Anggil Nopra; Susanto, Perengki; Abror, Abror; Risdwiyanto, Andriya (Universitas Proklamasi 45, 2025)
This study systematically examines the evolution and integration of the Entrepreneurial Marketing Orientation (EMO) concept into the Green Entrepreneurial Marketing Orientation (GEMO) framework, as well as its role in enhancing sustainable performance within the small and medium-sized enterprise (SME) sector. Employing a Systematic Literature Review (SLR) and bibliometric analysis using VOSviewer, this research maps the intellectual structure and emerging trends in GEMO studies during the 2020-2025 period. The findings reveal that GEMO represents an integrated capability rooted in Entrepreneurial Marketing Orientation, grounded in the Resource-Based View (RBV) and Dynamic Capabilities View (DCV) frameworks, where resilience and sustainability serve as the foundations of long-term competitive advantage. The integration of Green Entrepreneurial Orientation (GEO), Green Marketing Orientation (GMO), and Green Innovation (GI) creates an adaptive system that enhances organizational resilience against environmental, digital, and regulatory pressures. Furthermore, this study recommends the development of the Green Digital Entrepreneurial Marketing Orientation (GDEMO) concept to strengthen green innovation and organizational resilience in the era of Green Economy 5.0.